Creativity as a Means to Well-Being in Times of COVID-19 Pandemic: Results of a Cross-Cultural Study - Tang, Min; Hofreiter, Sebastian; Reiter-Palmon, Roni; Bai, Xinwen; Murugavel, Vignesh (Frontiers in Psychology, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has brought about unprecedented uncertainty and challenges to the worldwide economy and people’s everyday life. Anecdotal and scientific evidence has documented the existence of a positive relationship between the experience of crisis and creativity. Though this appears to be ubiquitous, the crisis-creativity-well-being relationship has not been sufficiently examined across countries and using a working adult sample. The current study drew on a sample consisting of 1,420 employees from China (n = 489, 40% females), Germany (n = 599, 47% females), and the United States (n = 332, 43% females) to examine whether creativity can function as an effective means to cope with crisis and to achieve both flourishing and social well-being. Multivariate analyses showed that perceived impact of COVID-19 was positively related to creative process engagement, which was positively related to employees’ self-reported creative growth. Creative growth was associated with a higher level of flourishing well-being. This sequential mediation model was significant across the three samples. Creativity also mediated the relationship between perceived impact of COVID-19 and social well-being (social connectedness), but this connection was only found for the Chinese sample. Further data analyses revealed that individualism moderated this serial mediation model in that the positive coping effect of creativity on both flourishing and social well-being was stronger for individuals who hold more collectivistic views. Results of the study have implications for crisis management, personal development, and positive functioning of individuals and society.